The Organizational Culture of Extra-large Secondary Schools in Bang Phli District under the Samut Prakan Secondary Educational Service Area Office - Nakmusik, Apisit; Aiemphaya, Kanporn (Journal of Humanities and Social Sciences, Rajapruk University, 2026)
The purposes of this research were to 1) study the organizational culture of large-sized secondary schools in Bang Phli District, under Samut Prakan Secondary Education Service Area; and 2) compare the organizational culture of large-sized secondary schools in Bang Phli District, under Samut Prakan Secondary Education Service Area, According to the teacher’s opinion classified by gender, educational qualification, school size, and work experience. The sample group used in this research consisted of teachers in educational institutions under the Samut Prakan Secondary Education Service Area in the academic year 2023. The sample size was determined using the Krejcie and Morgan table, yielding 113 individuals. Stratified random sampling was employed by proportionally matching the population to the determined sample size, followed by simple random sampling. The research instrument was a 5-level rating scale questionnaire with a reliability of .88. Data were analyzed using basic statistics, including frequency, percentage, mean, and standard deviation, and inferential statistics, namely the t-test and one-way analysis of variance. The results of the research were as follows: 1) The organizational culture of extra-large secondary schools in Bang Phli District under Samut Prakan Secondary Educational Service Area Office, was at a high level overall. When considering each aspect, the organizational culture of extra-large secondary schools was at a high level. Decision-making ranked first, followed by feeling of belonging, and acceptance ranked last. 2) Comparative results of the organizational culture of extra-large secondary schools in Bang Phli District under Samut Prakan Secondary Educational Service Area Office, showed that the organizational culture of extra-large secondary schools in Bang Phli District, Samut Prakan Secondary Educational Service Area Office, classified by educational qualifications, overall, was significantly different at the .05 level; otherwise, there was no difference.